Daya Ikat Putusan Mahkamah Internasional: Analisis Penyerangan Militer dan Paramiliter Amerika Terhadap Nikaragua - Fahri, Faizal (Fakultas Hukum Universitas Negeri Semarang, 2021)
The problem raised in this paper is that the use of military and paramilitary forces carried out by America violates state sovereignty and international law regarding state relations (America and Nicaragua). State sovereignty gives the right of responsibility to protect the sovereignty of its people, respect and fulfill the rights of its citizens and cooperate in the international community. However, in this dispute, state sovereignty is violated by internal members of the country, especially by members of the American military and paramilitaries. Although America believes the use of force by military and paramilitary members as a means of self-defense. This study was conducted by examining relevant decisions and facts from international law, customary international law, general principles of law, international treaties, conventions, declarations and decisions of international Court of Justice (ICJ). The Nicaragua case is a legal dispute that falls under the jurisdiction of the International Court of Justice in which Nicaragua has adopted methods in accordance with international legal procedures but the United States has rejected the decision of the International Court of Justice.